Not yet another negative trial-ReACTing on recent glioblastoma trials - Wick, Wolfgang; Wagener, Jan Robin (Clinical cancer research, 2020)
The present ReACT trial provides data from a small randomized controlled vaccination trial that in addition to other recent immunotherapy trials in glioblastoma allows sketching a rational, advanced trial design for the development of (immune) therapies in glioblastoma elaborating on but not restricting to biological monitoring and endpoints.See related article by Reardon et al., p. 1586